Effect of Electrolytic Plasma Processing on the Removal of Surface Scale for Fe6.5Si Alloy. Issue 3 (30th January 2017) - Gui, Wanyuan; Lin, Junpin; Hao, Guojian; Qu, Yuhai; Jiang, Zhipeng; Cheng, Fang; Liang, Yongfeng; Zhang, Hui
Abstract: The principal purpose of this study is to develop an innovation technology for effectively removing surface scale of Fe6.5Si alloy. The surface cleaning of rolled Fe6.5Si alloy has been carried out by electrolytic plasma processing (EPP) for various intervals with an optimized parameters. The characterization analyses confirm that the oxide scale of the rolled steel almost completely disappears after EPP treatment of 40 s. In the meanwhile, the EPP treated surface exhibits the occurrence of relatively fine structure and crater feature due to high power of plasma discharge. It is also found that EPP cleaning has no detrimental impact on the bulk properties of the steel. The effective cleaning of the EPP provides a guidance in surface modification of Fe6.5Si alloy and other metallic materials for future application. Abstract : In this study, electrolytic plasma processing (EPP) has been developed as an effective and innovation approach for removing surface scale and contaminants of Fe6.5Si alloy. This research has made an important progress toward surface cleaning and modification of Fe6.5Si alloy for its favorable application, and the development and optimization of EPP can be directed for its extended application in the high silicon steel and other metallic materials.